Erosivity index (EI30) for Lages (SC) - Bertol, Ildegardis (Pesquisa Agropecuaria Brasileira, 1993)
This work was done at the Centro de Ciências Agroveterinárias, in Lages, SC, Brazil, with the objective of determining the rainfall erosivity, its annual distribution and its relation with the precipitation. For the rainfall erosivity calculation the method proposed by Wischmeier modified by Cabeda was used. The rainfall coefficient (Rc), as proposed by Fournier, modified by Lombardi Neto, and the relations were made by the linear regression. The results showed mean annual erosivity index (EI30) equal to 5,694 MJ.mm/ha.h.year. During the October–February period, the annual total EI30 was 56% with special notability for February, with 16%. The equations determined were: EI30 = 0,06P + 110,46 (r = 0,58) and EI30 = 0,0lRc + 6,93 (r = 0,61), respectively for precipitation (P) and rainfall coefficient (Rc).